Persepsi Pegawai Mengenai Pengaruh Kompetensi Pegawai dan Kepuasan Kerja Terhadap Kinerja Organisasi dengan Sistem Pengendalian Intern Pemerintah dan Nilai-Nilai Organisasi Sebagai Variabel Moderasi (Studi pada Direktorat Jenderal Pajak di Lingkungan Kantor Wilayah Jawa Timur I Surabaya) - Suryanto, Dedy; Subroto, Bambang; Andayani, Wuryan (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
The purpose of this research is to examine and to provide evidence empirically influence of employees competence, and job satisfaction on organizational performance with government intern control systems and organizational values as moderating variables. Respondents of this study are 245 employees in thirty tax office in East Java I Region. The results show that organizational performance is affected by employees competence and job satisfaction. Other result, improved organizational performance can be achieved better when employees competence and job satisfaction moderated by organizational values. This study also found that organizational performance can be achieved better if employees competence are improved and moderated by government intern control systems, however, organizational performance can’t achieved better, although job satisfaction are improved and moderated by government intern control system.